Detection of Clostridium difﬁcile associated diarrhea in disease based on Polymerase chain reaction and bacterial culture And toxin A, B frequency - mohsen zargar; ali javadi; abbas morovvati (Fasa University of Medical Sciences, 2019)
Detection of Clostridium Difﬁcile Associated Diarrhea in Disease Based on Polymerase Chain Reaction and Bacterial Culture and Toxin A, B Frequency Detection of Clostridium Difﬁcile Associated Diarrhea in Disease Background & Objective: Clostridium difﬁcile is an obligate anaerobic, gram positive bacillus. The purpose of this study was to comparison between PCR technique and bacterial culture for assessing the prevalence of Clostridium difﬁcile infection in the samples of watery diarrhea. Materials & methods: This cross-sectional qualitative study was performed in 68 samples of watery diarrhea in Qom province hospitals. All samples were cultured in the specialized CCFA Agar medium. Specific primers were applied for the PCR Assay based on cdd3 gene. Based on this primer PCR product for this gene must be 622bp.toxin A & B diagnosis based on specific primers and product must be 473 and 272 bp Results: In this study, the optimized PCR technique was determined to be bacterium in 16 samples. But bacteria diagnosis in 11 samples by culture method. 6 samples have toxin A and B, 4samples has toxin A and 3 samples has toxin B. Conclusion: Cytotoxicity method is gold standard for clostridium difﬁcile. Diagnosis of these bacteria is very important and PCR was found as an applicable, sensitive, and quick technique for detection of Clostridium difﬁcile in compromise culture medium method.